Theories and practices of development - Willis, Katie (London Routledge, 2011)
Theories and Practices of Development provides a clear and user-friendly introduction to the complex debates around how development has been understood and achieved. The second edition has been fully updated and expanded to reflect global political and economic shifts, as well as new approaches to development. The rise of China and India is given particular attention, as is the global economic crisis and its implications for development theories and practice. There are new sections on faith-based development, and the development dimensions of climate change, as well as greater engagement with development theories as they are put into practice in the Global North.
Rev. ed. of: Theories and practices of development. 2005.
Keywords: Economic development